2011
DOI: 10.1128/iai.01274-10
|View full text |Cite
|
Sign up to set email alerts
|

The OspE-Related Proteins Inhibit Complement Deposition and Enhance Serum Resistance of Borrelia burgdorferi , the Lyme Disease Spirochete

Abstract: Borrelia burgdorferi, the Lyme disease spirochete, binds the host complement inhibitors factor H (FH) and FH-like protein 1 (FHL-1). Binding of FH/FHL-1 by the B. burgdorferi proteins CspA and the OspE-related proteins is thought to enhance resistance to serum-mediated killing. While previous reports have shown that CspA confers serum resistance in B. burgdorferi, it is unclear whether the OspE-related proteins are relevant in B. burgdorferi serum resistance when OspE is expressed on the borrelial surface. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 47 publications
0
42
0
Order By: Relevance
“…Synthetic DNAs were produced by IDT (Coralville, IA). Oligonucleotide P50F (Table 1) was 32 P labeled at the 5= terminus using T4 polynucleotide kinase (New England BioLabs, Beverly, MA) and [␥-32 P]ATP (ICN Radiochemicals, Irvine, CA) (44). Unincorporated [␥-32 P]ATP was removed with Sephadex G-10 centrifuge columns (GE Healthcare, Little Chalfont, United Kingdom) equilibrated with TE buffer (100 mM Tris-HCl, pH 8.0, 10 mM EDTA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthetic DNAs were produced by IDT (Coralville, IA). Oligonucleotide P50F (Table 1) was 32 P labeled at the 5= terminus using T4 polynucleotide kinase (New England BioLabs, Beverly, MA) and [␥-32 P]ATP (ICN Radiochemicals, Irvine, CA) (44). Unincorporated [␥-32 P]ATP was removed with Sephadex G-10 centrifuge columns (GE Healthcare, Little Chalfont, United Kingdom) equilibrated with TE buffer (100 mM Tris-HCl, pH 8.0, 10 mM EDTA).…”
Section: Methodsmentioning
confidence: 99%
“…The cp32 elements of Lyme disease spirochetes, such as B. burgdorferi, are of particular interest, since they encode Erp, RevA, and Mlp lipoproteins. These bacterial surface proteins are produced by the bacterium during mammalian infection, and those with known functions serve as adhesins for host components, such as plasmin(ogen), laminin, and complement factor H (1,7,8,9,10,13,22,25,26,32,33,38,42,43,49,63). Sequences of the erp, revA, and mlp loci generally vary between different cp32s (Fig.…”
mentioning
confidence: 99%
“…Research on the borrelial Erp outer surface proteins has revealed multiple properties associated with mammalian infection (2,3,11,12,34,37,40,45,59). Given what is known of their functions, it is not surprising that B. burgdorferi Erp proteins are produced during mammalian infection but repressed during colonization of tick vectors (10,31,48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Erp proteins are located in the bacterial outer membrane and are exposed to the external environment (25,32,41). Known functions of Erp proteins include binding of host plasmin(ogen), laminin, and the complement regulators factor H and factor H-related proteins 1, 2, and 5 (2,3,11,12,34,37,40,45,59). These functions indicate roles for Erp proteins in host adherence, dissemination, and resistance to the alternative pathway of complement-mediated killing.…”
mentioning
confidence: 99%
“…Borrelia organisms, including B. burgdorferi B31, B. burgdorferi JD1, B. garinii Pbi, and B. garinii IP90, were cultivated at 34°C in BSK-II medium containing 6% heat-inactivated rabbit serum (BSK-II complete, pH 7.6) (37). For surface localization immunofluorescence and Triton X-114 phase partitioning experiments, we utilized the avirulent, high-passage-number strain B. burgdorferi clone F (cF), which was described previously (38,39).…”
Section: Methodsmentioning
confidence: 99%